SELF-EFFICACY AS A FACTOR OF PROFESSIONALIZATION OF STUDENTS - Muzуka Olena (Educological discourse, 2018)
The article deals with the peculiarities of self-efficacy of freshmen students. The structure and possibilities of development of separate components of self-efficacy in educational-professional activity are analyzed. The results of empirical research are described and and assumptions made about inter- and intra-subjective conditions for the inclusion of self-efficacy in value-motivational regulatory processes that promote the professionalization of students. According to the results of the study, first-year students are generally determined by a rather high level of self-efficacy, which is an indicator of psychological readiness for profession. The formation of professional self-efficacy is largely influenced by the conditions of the social environment and educational and professional activities. Self-efficacy is based on value experience and internal standards of activity, defines the direction and motivation of a person. In this regard, self-efficacy is one of the most important factors for the successful professionalization of students.